(untitled) (Research, Society and Development, 2021)
The study aims to evaluate how the prior knowledge of health professionals about self-care in leprosy in the Family Health Strategies in the city of Icó-CE is presented. This is an exploratory field study with a quantitative and qualitative approach that was carried out during the months of January and February 2021 in the city of Icó, located in the Center-South region of the state of Ceará. The sample consisted of 11 health professionals who accompany patients with leprosy from eight Family Health Strategies in the city of Icó-CE, with a predominance of females (11.1% men and 88.8% women). It is noteworthy that 88.8% of respondents already had some course or knowledge about leprosy. The data obtained from this study are similar to the literature, revealing flawed educational and practical aspects about leprosy, which allowed to know the level of knowledge of health professionals about the disease, as well as to understand the repercussions that can be caused in the leprosy patients due to failure of health management in the process of continuing education and updates. Recognizing these limitations and having strategies to transform them in favor of continuous training in health education and updates among members of the interprofessional team are challenges to make it possible to make advances in the self-care practices and autonomy of the leprosy patient in relation to the treatment and disease.